Metabolic engineering of Bacillus subtilis for enhancing riboflavin production by alleviating dissolved oxygen limitation. (August 2021) - You, Jiajia; Yang, Chen; Pan, Xuewei; Hu, Mengkai; Du, Yuxuan; Osire, Tolbert; Yang, Taowei; Rao, Zhiming
Graphical abstract: Highlights: Hypoxia induced down regulation of purine metabolism related genes and up regulation of nitrogen metabolism genes tnrA and glnR in B. subtilis . Knockout of the purR and knockdown of the tnrA and glnR genes significantly increased the production of riboflavin. Dynamically control the expression of the vgb gene, and further increase the production of riboflavin by increasing the utilization of oxygen by the cells. The final engineered strain had increased riboflavin production by 45.51% compared to the initial strain. Abstract: Riboflavin, an essential vitamin for animals, is used widely in the pharmaceutical industry and as a food and feed additive. The microbial synthesis of riboflavin requires a large amount of oxygen, which limits the industrial-scale production of the vitamin. In this study, a metabolic engineering strategy based on transcriptome analysis was identified as effective in increasing riboflavin production. First, transcriptional profiling revealed that hypoxia affects purine, and nitrogen metabolism. Next, the precursor supply pool was increased by purR knockout and tnrA and glnR knockdown to balance intracellular nitrogen metabolism. Finally, increased oxygen utilization was achieved by dynamically regulating vgb . Fed-batch fermentation of the engineered strain in a 5-liter bioreactor produced 10.71 g/l riboflavin, a 45.51% higher yield than that obtained with Bacillus subtilis RF1. The metabolic engineering strategy described herein is useful for alleviating the oxygen limitation of bacterial strains used for the industrial production of riboflavin and related products.